Study of deformation law and support design feasibility of right-angled trapezoidal roadways - Chen, Feng; Wang, Xuebin; Bai, Xueyuan (Frontiers in Earth Science, 2023)
Given the problems of serious asymmetric deformation and the difficulty in supporting right-angled trapezoidal roadways during the mining process, we established a mechanical model of surrounding rock for a right-angled trapezoidal roadway, determined the relationship between the deflection and tilt angle of the roadway roof, and determined that the typical failure mode of right-angled trapezoidal roadways is the upper slip of the high side. Two optimized support schemes are proposed, in which a constant resistance large deformation (CRLD) bolt + ordinary I-steel or a portal energy absorbing hydraulic (PEAH) support + ordinary bolt is used as the main support instead of an ordinary bolt + ordinary I-steel. Numerical simulation analysis shows that the aforementioned optimized support schemes can reduce the deformation, acoustic emission (AE) quantity, and AE energy of rock surrounding roadways and change how surrounding rock releases energy from main earthquake type to swarm earthquake type. The support scheme with CRLD bolt + ordinary I-steel or PEAH support + ordinary bolt as the main support can reduce the deformation of a roadway’s high side to 0.192 and 0.145 m, respectively. This shows that the two optimized schemes can effectively improve the overall bearing capacity and integrity of the rock surrounding roadways, which can be applied in the field.